2021
DOI: 10.1111/ijcs.12722
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ purchase behaviour and green marketing: A synthesis, review and agenda

Abstract: The study presents an overview of green marketing and the gap between attitude and actual purchase behaviour of consumers towards green products. A total of 232 studies have been analysed using a systematic review to develop a green purchase decision‐making model. A thematic analysis helped in the identification of three major themes namely; personal factors affecting green purchase; green purchase; and green marketing mix. The concern for eco‐environment, eco‐labelling, past experiences and perceived usefulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
93
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(142 citation statements)
references
References 204 publications
(257 reference statements)
0
93
0
4
Order By: Relevance
“…The results of this study are expected to be able to help marketer to understand the factors that affect consumers to purchase green product or carry out green purchase behavior, thus they can build a strategy in order to respond to this condition. This study also fills the research gap and respond to the recommendation from the study from Clayton et al (2016), Thomas et al (2016), andSharma (2021) that there is a need to understand and drive consumer behavior on green marketing, which also include green purchase behavior while paying attention to the environment.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…The results of this study are expected to be able to help marketer to understand the factors that affect consumers to purchase green product or carry out green purchase behavior, thus they can build a strategy in order to respond to this condition. This study also fills the research gap and respond to the recommendation from the study from Clayton et al (2016), Thomas et al (2016), andSharma (2021) that there is a need to understand and drive consumer behavior on green marketing, which also include green purchase behavior while paying attention to the environment.…”
mentioning
confidence: 82%
“…The second antecedent of green purchase behavior is green brand. Green brand can be understood as a brand that is associated by consumers with environmental conservation and sustainable business practices (Sharma, 2021;Sarkar et al, 2019). González-Rodríguez et al (2020) explained that green brand can also be referred to as brand association that fall into the unique category, as its function is to attract consumers to become more aware of the need to protect the environment and maintain it in order to get a unique selling value for a product.…”
Section: Literature Review Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitude captures consumers' evaluation of perceived benefit and cost implications of green products consumption [23]. Previous green marketing studies have noted that consumer attitude toward green products or services significantly influences green purchase intention [1,12,13,24,25].…”
Section: Theoretical Framework and Hypotheses Development 21 Green Knowledge Innovativeness And Attitudementioning
confidence: 99%
“…Many earlier studies have identified numerous factors affecting consumers' green attitude and purchase behavior [1,[9][10][11][12][13][14][15][16]. In the financial services sector, however, there has been little research on the factors influencing green consumption behavior, with notable exceptions [8,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%